A Cyber Secure and Scalable Blockchain-Based Framework for Monitoring and Controlling Distributed Energy Resources - Raifa Akkaoui; Peter Palensky; Dick H. J. Epema; Alexandru Stefanov (IEEE Access)
The ever-growing share of behind-the-meter distributed energy resources (DERs) is radically reshaping conventional distribution systems by incorporating advanced control and monitoring schemes. However, the efficiency and reliability of these mechanisms profoundly depend on the integrity of the data (e.g., measurements, control commands, etc.) exchanged among this ecosystem’s stakeholders (i.e., prosumers, aggregators and grid operators). Besides, traditional power systems depend solely on trusted aggregators for the collection of these DERs’ data, which might jeopardise the security of the whole system if these aggregators are compromised. Thus, in this paper, we address these concerns by proposing a hierarchical blockchain-based framework that incorporates a distributed integrity auditing scheme for DERs’ measurements. Specifically, by leveraging hash functions and Merkle trees, a secure and lightweight blockchain-based hash aggregation protocol is designed to ensure the authenticity of behind-the-meter DERs’ measurements. Further, an automated distributed sanity-check of DERs’ set-points (i.e., control commands) is also proposed to mitigate the risk of coordinated cyber-attacks on large shares of DERs. The proposed framework is implemented and evaluated under various scenarios to assess its effectiveness and security. The obtained results indicate the scalability of the framework as it is capable of achieving a reduction of roughly 47% and 44% in terms of its runtime and storage overheads.